Learning Mergers & Acquisitions: Blockchain - Julio Rionaldo Alang (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
The Mergers & Acquisitions process are characterized by the fact that companies rely so much on attorneys, external deal advisors, auditors, tax consultants and other sorts of professional intermediaries. This results in both, high costs and considerable time expenditure. The lengthy and cost-intensive process makes it particularly difficult for enterprises to profit from any Mergers & Acquisitions transactions. In However, with the advent of Cryptocurrencies, Initial Coin Offerings, and Blockchain implementation, Blockchain and Machine-Learning as technology can be used across the whole bandwidth of the Mergers & Acquisition process, from letters of intent, asset to equity sales, through all stages of the due diligence into post-transactions integration. In this article, the researcher will explore and further elaborate on the comprehensive Mergers & Acquisitions process within the Blockchain.